A dual-targeting AS1411-folic acid fluorescent nanocomposite for cancer cell and drug delivery. Issue 17 (19th April 2018) - Ai, Jun; Ga, Lu; Wang, Yong
Abstract : In this paper, we report a novel approach for AS1411 G-quadruplex and folic acid-templated dual-targeting fluorescent Au nanocomposite with DOX and its application to bioimaging. Abstract : In this paper, we report a novel approach for AS1411 G-quadruplex and folic acid-templated dual-targeting fluorescent Au nanocomposite with DOX and its application to bioimaging. For the first time, we demonstrate the method of generating AS1411-folic acid DOX-conjugated gold nanocomposite (AF-D-AuNPs) in aqueous solution for increasing targeting ability.